Den betingede accept - Torsten Kolind (Nordisk Tidsskrift for Kriminalvidenskab)
This article focuses on aspects of identity and social order in relation to the interaction between the larger society and ex-prisoners seeking to live a normal life without criminality. It is argued that while this interaction and the apparent re-acceptance of the ex-prisoner appear unproblematic on the surface, they are nonetheless ruled by what the author calls conditional acceptance. That is, the ex-prisoner must demonstrate his worthiness by accepting himself as normal and at the same time withdrawing from situations, practices and attitudes where members of the larger society would have difficulties in supporting this normality. Conditional acceptance tends to leave the ex-prisoner in conflict: he is neither fully conformist nor fully deviant. In regard to identity, this vacuum and the conditions it entails, leave the ex-prisoner badly equipped in his attempt to live up to the demands of our modern western ideology of identity - demands such as authenticity, coherence, prestige and responsibility.